2007
DOI: 10.1002/csr.160
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social and environmental responsibility in Asian countries and other geographical regions

Abstract: This study examines two aspects of corporate social responsibility (social and environmental CSR) in 15 Asian countries. The performance of fi rms in these Asian countries on the two types of CSR is also assessed relative to country economic, political and social conditions, and compared with those of other regions (Western Europe, East/Central Europe, Australia/New Zealand, US/Canada, Middle East and Africa). Drawing from over 8700 surveys of fi rms in 104 countries, this study demonstrates substantial countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
395
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(417 citation statements)
references
References 40 publications
16
395
0
6
Order By: Relevance
“…Consistent with several studies (Williams, 1999;Freedman and Stagliano, 1992;Meek et al, 1995;Fekrat et al, 1996;Gamble et al, 1996;Williams and Wern Pei, 1999;Buhr and Friedman, 2001;Xiao et al, 2005;van der Laan Smith et al, 2005;Baughn et al, 2007), that have attempted to observe that the country of origin is an important determinant of sustainability disclosure practices, we found differences in the corporate disclosure between Spanish and Brazilian companies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with several studies (Williams, 1999;Freedman and Stagliano, 1992;Meek et al, 1995;Fekrat et al, 1996;Gamble et al, 1996;Williams and Wern Pei, 1999;Buhr and Friedman, 2001;Xiao et al, 2005;van der Laan Smith et al, 2005;Baughn et al, 2007), that have attempted to observe that the country of origin is an important determinant of sustainability disclosure practices, we found differences in the corporate disclosure between Spanish and Brazilian companies.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, several studies (Williams, 1999;Freedman and Stagliano, 1992;Meek et al, 1995;Fekrat et al, 1996;Gamble et al, 1996;Williams and Wern Pei, 1999;Buhr and Friedman, 2001;Xiao et al, 2005;van der Laan Smith et al, 2005;Baughn et al, 2007) have attempted to observe the country effect by analysing CSR reports in a cross-national context. These reports have shown that the country of origin is an important determinant of sustainability disclosure practices.…”
Section: Corporate Social Responsibility Reportsmentioning
confidence: 99%
“…The GDPPC is incorporated as a control variable to measure the effects of the economic conditions of a country, because higher levels of economic development could lead to higher levels of CSR activities and more sustainability reporting (Baughn et al, 2007;Li et al, 2010). The GDPPC data (current US$) is obtained from the World Bank.…”
Section: Independent and Control Variablesmentioning
confidence: 99%
“…Namely, comparing to their counterparts in the middle and western regions of China, firms in eastern regions enjoy more benefits in M&A performance by fulfilling CSR. Compared to other studies that focus on CSR differences across regions [42][43][44], this paper further explores different CSR-performance linkages across regions. Our study indicates that different markets, legal requirements, and governance environments might have significant effects on CSR-performance linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Kolk et al (2015) [43] conducted a survey in China and found that Chinese customers perceive two components (instead of four) in Western CSR constructs. Baughn et al (2007) [44] conducted a survey in 104 countries and found that CSR is different across countries and regions. Baughn also found that significant relationships exist between CSR and a country's economic, political, and social contexts.…”
Section: Csr Geographical Regions and Long-term Manda Performancementioning
confidence: 99%